The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1044/0161-1461(2009/08-0001)
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Morphological Awareness on the Literacy Development of First-Grade Children

Abstract: Children as young as first graders evidenced morphological awareness, and morphological awareness influenced the children's literacy development. Theoretical implications of the findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 28 publications
1
88
0
15
Order By: Relevance
“…A number of studies reported a positive correlation between good reading, spelling and the use of morphological connections in tasks concerning spoken and written language (Carlisle, 1987;Fischer et al, 1985;Wolter, Wood, & D'zatko, 2009). Based on these studies, it appears that morphological analysis in reading is important to developing skills in reading and spelling.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…A number of studies reported a positive correlation between good reading, spelling and the use of morphological connections in tasks concerning spoken and written language (Carlisle, 1987;Fischer et al, 1985;Wolter, Wood, & D'zatko, 2009). Based on these studies, it appears that morphological analysis in reading is important to developing skills in reading and spelling.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…Morphological awareness includes knowledge about the meaningful parts of words including word roots (e.g., dieter, dietician) and affixes (e.g., uneasy, bussed, lazy etc.) (e.g., Wolter, Wood, & D'zatko, 2009).…”
Section: Teachers' Metalinguistic Knowledge For Spelling Instructionmentioning
confidence: 99%
“…Medvetenhet om morfem har tydliga och positiva effekter på barns ordavkodning och stavning (Kirk & Gillon, 2009;Wolter, Wood, & D´zatko, 2009). Att stimulera barns morfologiska medvetenhet kan exempelvis göras genom att analysera sammansatta ord eller genom att identifiera, ta bort och lägga till stavelser i ord (Vetenskapsrådet, 2015).…”
Section: Faktorer Av Betydelse För Läs-och Skrivutvecklingenunclassified
“…Att stimulera barns morfologiska medvetenhet kan exempelvis göras genom att analysera sammansatta ord eller genom att identifiera, ta bort och lägga till stavelser i ord (Vetenskapsrådet, 2015). I en studie gjord av Wolter et al, (2009) framkommer att barn som gick i första klass redan var morfologiskt medvetna och att de använde sin morfologiska kunskap när de stavade ord. Detta betyder att den morfologiska kunskapen kan stimuleras tidigare hos barn än i första klass.…”
Section: Faktorer Av Betydelse För Läs-och Skrivutvecklingenunclassified
See 1 more Smart Citation